Diagnostic accuracy of tri-ponderal mass index and body mass index in estimating overweight and obesity in South African children - Violet K. Moselakgomo; Marlise van Staden (AOSIS, 2019)
Background: Prevalence of obesity in youths has drastically increased in both industrialised and non-industrialised countries, and this transition resulted in an increased prevalence of chronic diseases. Aim: The study aimed to comparatively examine prevalence of overweight and obesity status based on tri-ponderal mass index and body mass index in estimating body fat levels in South African children. Setting: The study was conducted in Limpopo and Mpumalanga provinces of South Africa. Methods: A cross-sectional survey of 1361 (boys: n = 678; girls: n = 683) children aged 9-13 years was undertaken. The children's age and sex-related measurements of body weight, waist-to-height ratio, waist-to-hip ratio, triceps skinfold, subscapular skinfolds and sum of skinfold were taken using the International Society for Advancement of Kinanthropometry protocol. TMI and BMI calculations classified children according to weight and age categories. Descriptive statistics, Spearman's correlations and multiple linear regression analyses were set at ≤ 0.05. Results: Obesity classifications on TMI and BMI among children were as follows: Boys: 7.3%, 2.6%; 2.2%, 0.7%; Girls: 4.0%, 1.0%; 1.8%, 0.6%. Body weight, WHtR, WHpR, TSKF, SSKF and ΣSKF significantly correlated with TMI (r = 0.40, p 0.001; r = 0.73, p 0.001; r = −0.09, p 0.001; r = 0.50, p 0.001; r = 0.51, p 0.001 and r = 0.52, p 0.001) and BMI (r = 0.81, p 0.001; r = 0.59, p 0.001; r = −0.22, p 0.001; r = 0.63, p 0.001; r = 0.67, p 0.001 and r = 0.66, p 0.001). Regression analysis revealed that body weight, WHtR, WHpR, TSKF, SSKF and ΣSKF accounted for 65% and 85% of variance in children's TMI (R2 = 0.647, F[6 1354] = 413.977, p 0.001) and BMI (R2 = 0.851, F[6 1354] = 1288.218, p 0.001). Conclusion: TMI revealed strikingly higher incidence of overweight and obesity in South African boys and girls than BMI. Future studies are needed to clarify sensitivity of TMI over BMI in quantifying obesity prevalence in children and adolescents.